Design of Analog Signal Processing Applications Using Carbon Nanotube Field Effect Transistor-Based Low-Power Folded Cascode Operational Amplifier - Varsha S. Bendre; A. K. Kureshi; Saurabh Waykole (Journal of Nanotechnology)
Carbon nanotube (CNT) is one of the embryonic technologies within recent inventions towards miniaturization of semiconductor devices and is gaining much attention due to very high throughput and very extensive series of applications in various analog/mixed signal applications of today’s high-speed era. The carbon nanotube field effect transistors (CNFETs) have been reconnoitred as the stimulating aspirant for the future generations of integrated circuit (IC) devices. CNFETs are being widely deliberated as probable replacement to silicon MOSFETs also. In this paper, different analog signal processing applications such as inverting amplifier, noninverting amplifier, summer, subtractor, differentiator, integrator, half-wave and full-wave rectifiers, clipper, clamper, inverting and noninverting comparators, peak detector, and zero crossing detector are implemented using low-power folded cascode operational amplifier (op-amp) implemented using CNFET. The proposed CNFET-based analog signal processing applications are instigated at 32 nm technology node. Simulation results show that the proposed applications are properly implemented using novel folded cascode operational amplifier (FCOA) implemented using CNFET.